HUBUNGAN PENGETAHUAN DAN INFORMASI DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR - Sunirah, Sunirah; Azhara, Kana; Wahiroh, Wahiroh (JOURNAL OF HEALTH SCIENCE, 2021)
Breast milk is the best nutrition for babies because the composition of nutrients in it is optimally able to ensure the growth of the baby's body, the quality of the nutrients is also the best because it is easily absorbed and digested by the baby's intestines, so the use of breast milk in Indonesia needs to be increased. Basically there are various kinds of breast milk, one of which is colostrum. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all mothers who had babies, totaling 40 pregnant women. The sample of this research used systematic random sampling method. The sample of this study amounted to 40 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis showed that there was a relationship of knowledge (p value = 0.002) and there was a relationship of information (p value = 0.001) with giving colostrum to newborns. Suggestions are expected for health workers to provide complete communication, information and education to the community in the work area about giving colostrum to newborns. Keywords: Giving Colostrum to Newborns